(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Legal aid services play a crucial role in ensuring access to justice and legal representation for individuals who may not have the financial means to hire private attorneys. Legal aid services are typically provided by government-funded agencies, nonprofit organizations, or pro bono lawyers, and they aim to bridge the justice gap and ensure that everyone, regardless of their economic status, can assert their legal rights and navigate the legal system